Experience in the teaching work from the pedagogical research practice of deepening. - Londoño Celis, Yuly Jasbleidy (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This reflective article provides knowledge about the Deepening Investigative Pedagogical Practice, through experience and a personal point of view on the different activities carried out by teachers in training from the educational field. Thus, it is developed around the qualitative paradigm with a phenomenological approach, taking into account as an instrument the field diaries and the information collection matrix to publicize the educational experiences that were obtained in the development of the Investigative Pedagogical Practice. Deepening as a teacher in training. For this reason, it is important to highlight various authors who talk about pedagogical practice, the role of the teacher, the role of the student and highlight their own experience in educational practice as a teacher in training, in order to publicize the different challenges and opportunities faced by the students of the Bachelor of Basic Education with an emphasis on Mathematics, Humanities and Spanish Language of the Pedagogical and Technological University of Colombia, in the development of the Deepening Investigative Pedagogical Practice in X semester, when exercising their teaching duties . According to the above, it can be concluded that it is very important to recognize the educational processes and the experiences in the academic and labor training of teachers in training, since it generates awareness about the importance of practices and allows progress in the creation of other possible more constant, rigorous and complete pedagogical practices from the first semesters of this program, allowing students of this degree to participate in a real teaching environment.